PENGALAMAN REMAJA PUTRI SELAMA KEHAMILAN DI WILAYAH KERJA PUSKESMAS KLUNGKUNG I - Monica Monica; I Nyoman Sutarsa (E-Jurnal Medika Udayana, 2015)
EXPERIENCE OF YOUNG WOMEN WITH PREGNANCY IN KLUNGKUNG I PRIMARY HEALTH CARE COVERAGEThe high proportion of pregnancies at an early age greatly impact in the field of health and social teenagers. Visits cases of pregnant women with age less than 20 years in the health center Klungkung I kept popping with proportion range of 3.9% -5.17% per year since 2010. This research was conducted to find out how young women experience during pregnancy in Puskesmas Klungkung I. This study used a qualitative descriptive research design. Samples were selected purposively. Data were collected through interviews. Analysis of data using thematic analysis method. Research conducted at the health center first Klungkung on August 7 to September 6, 2014. A total of 6 respondents follow research by the characteristics of the age of 17, 18, 19 years with the last education elementary, junior high and high school. The results showed young women experiences during pregnancy were diverse and depend on the situation experienced by each adolescent. How young women to learn first pregnancy affects young women experience, personal stress, self-confidence and social pressure during pregnancy. Experience of adolescents is diverse and influenced by how the situation of young women learn their first pregnancy.